PERAN MANAJEMEN RESIKO DALAM MEMINIMALISIR RESIKO GAGAL BAYAR PADA PRODUK KEUANGAN SYARIAH - Ardan Nafik; Rini Puji Astuti; Silvia Maulida I’lana (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
Islamic financial institutions in Indonesia have made significant progress in recent years. This development is driven by the increasing public interest in financial products that comply with sharia principles. This study uses a qualitative method. This study uses a descriptive qualitative approach with a literature study method. The results of this study indicate that: The implementation of risk management in Islamic financial institutions, including Bank Syariah Indonesia (BSI), reflects compliance with Islamic principles in carrying out banking operations. The most common risk faced in Islamic financing is credit risk, especially in murabahah and ijarah products. This risk often arises due to the inability of customers to fulfill their obligations or due to unstable economic conditions. To anticipate this, BSI has implemented various mitigation strategies, such as strict selection of prospective customers, continuous monitoring after financing is provided, and the formation of risk reserves to deal with potential defaults. In addition, internal supervision by the Sharia Committee ensures that all products and policies implemented remain in accordance with Islamic values. Meanwhile, the Financial Services Authority (OJK) and the National Sharia Council as Indonesian Ulema Council (DSN-MUI) also play a role by establishing regulations that serve as guidelines for Islamic banks in managing and mitigating risk.